Teaching for moral imagination : an interdisciplinary exploration - Joseph, Pamela Bolotin (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2024)
"Teaching for Moral Imagination: An Interdisciplinary Exploration examines the multifaceted nature of morality and ethics, moral development, and moral education so to provide educators with a clear yet complex understanding of theories, issues, practices, and curricular content. This text is intended to be an accessible work of academic significance that inspires educators' deliberation about personal and societal values as well as approaches for fostering children's and adolescents' moral development, cultivating ethical classrooms and schools, and creating transformative moral education curricula. This book is organized by interrelated components: Moral philosophy, ethics, and moral imagination Human nature and morality Moral emotions and reasoning Culture, morality, and moral socialization Moral socialization in classrooms and schools Classrooms and schools as moral communities Moral education curricula Teachers' ethical professionalism and the moral imagination Teaching for Moral Imagination will be a pertinent text for teacher preparation courses that specifically focus on the moral dimensions of education as well as more comprehensive classes about teaching, teachers, and classroom culture. Such classes are offered in undergraduate and graduate teacher preparation programs, professional studies for experienced teachers, educational studies classes in the liberal arts, and doctoral seminars for students becoming teacher educators and educational leaders. This book also is intended as a source for teachers' professional development in schools and for reading groups. Finally, in our contemporary societies emphasizing extreme individualism, competition, conformity, and prejudice as well as unexamined beliefs leading to violence in words and actions, it is crucial to consider how schools can encourage ethical reasoning, compassion, and transformative alternatives for moral education"-- Provided by publisher.
Keywords: Moral education.; Interdisciplinary approach to knowledge.; Education -- Philosophy, Theory & Social Aspects.; Moral and social purpose of education.; Philosophy and theory of education.; elektronické knihy; electronic books